Factors Influencing the Acceptance of Online Shopping in Pakistan - Samra Chaudary; Sehrish Nisar; Muhammad Abdul Rehman (The Lahore Journal of Business)
The rapid growth of the Internet and its extended reach has helped developing countries adopt e-commerce, thus enabling consumers to make transactions worldwide. This study identifies the factors related to online shopping and examines consumer motivation and acceptance in this context. We employ exploratory factor analysis, structural equation modeling, and cluster analysis and find that Pakistani consumers behave very differently from consumers in Western countries or countries that have adopted online shopping on a wide scale. While factors such as convenience and trust are seen to affect consumer behavior, other variables such as perceived price and information availability are less importance. The study also examines the reasons for this deviation from typical consumer behavior.